Effectiveness of 10 and 13-valent pneumococcal conjugate vaccines against invasive pneumococcal disease in European children: SpIDnet observational multicentre study - Savulescu, Camelia; Krizova, Pavla; Valentiner-Branth, Palle; Ladhani, Shamez; Rinta-Kokko, Hanna; Levy, Corinne; Mereckiene, Jolita; Knol, Mirjam; Winje, Brita A; Ciruela, Pilar; de Miguel, Sara; Guevara, Marcela; et al. (Vaccine, 2022)
BACKGROUND: Pneumococcal conjugate vaccines covering 10 (PCV10) and 13 (PCV13) serotypes have been introduced in the infant immunization schedule of most European countries in 2010-11. To provide additional real-life data, we measured the effectiveness of PCV10 and PCV13 against invasive pneumococcal disease (IPD) in children of 12 European sites (SpIDnet). METHODS: We compared the vaccination status of PCV10 and PCV13 serotype IPD (cases) to that of nonPCV13 serotype IPD (controls) reported in 2012-2018. We calculated pooled effectiveness as (1-vaccination odds ratio)*100, and measured effectiveness over time since booster dose. RESULTS: The PCV13 and PCV10 studies included 2522 IPD cases from ten sites and 486 cases from four sites, respectively. The effectiveness of ≥ 1 PCV13 dose was 84.2% (95 %CI: 79.0-88.1) against PCV13 serotypes (n = 2353) and decreased from 93.1% (87.8-96.1) < 12 months to 85.1% (72.0-92.1) ≥ 24 months after booster dose. PCV13 effectiveness of ≥ 1 dose was 84.7% (55.7-94.7) against fatal PCV13 IPD, 64.5% (43.7-77.6), 83.2% (73.7-89.3) and 85.1% (67.6-93.1) against top serotypes 3, 19A and 1, respectively, and 85.4% (62.3-94.4) against 6C. Serotype 3 and 19A effectiveness declined more rapidly. PCV10 effectiveness of ≥ 1 dose was 84.8% (69.4-92.5) against PCV10 serotypes (n = 370), 27.2% (-187.6 to 81.6) and 85.3% (35.2-96.7) against top serotypes 1 and 7F, 32.5% (-28.3 to 64.5) and -14.4% (-526.5 to 79.1) against vaccine-related serotypes 19A and 6C, respectively. CONCLUSIONS: PCV10 and PCV13 provide similar protection against IPD due to the respective vaccine serotype groups but serotype-specific effectiveness varies by serotype and vaccine. PCV13 provided individual protection against serotype 3 and vaccine-related serotype 6C IPD. PCV10 effectiveness was not significant against vaccine-related serotypes 19A and 6C. PCV13 effectiveness declined with time after booster vaccination. This multinational study enabled measuring serotype-specific vaccine effectiveness with a precision rarely possible at the national level. Such large networks are crucial for the post-licensure evaluation of vaccines.
Keywords: Streptococcus pneumoniae; Serotype; pneumokokové vakcíny; Humans; pneumokokové infekce; Pneumococcal Vaccines; Serogroup; kojenec; Pneumococcal Infections; lidé; 13-valent pneumococcal vaccine; Infant; Immunization Schedule; očkovací schéma; Child; dítě; Vaccines, Conjugate; séroskupina; Invasive pneumococcal disease; 10-valent pneumococcal vaccine; vakcíny konjugované